PENGARUH MODEL PEMBELAJARAN BERPIKIR INDUKTIF TERHADAP HASIL BELAJAR SISWA KELAS X SMA PARULIAN 1 MEDAN - IRWAN SUSANTO (JURNAL PENELITIAN FISIKAWAN, 2020)
This study aims to determine the Effect of Inductive Thinking Learning Model on Student Learning Outcomes in Material Magnitude and Measurement in Class X Semester I Parulian 1 Medan High School T.P. 2019/2020. This type of research is quasi-experimental research (quasi-experimental). The population of this study is all students of class X Semester 1 Parulian 1 High School Medan which consists of 4 parallel classes. Sampling was done by cluster random sampling, which is class X-2 as an experimental class with 30 people taught by Inductive Thinking learning models and X-1 class as a control class amounting to 30 people who were taught using the Direct Learning model. The instruments in this study amounted to 23 items in the form of multiple choices with 4 options (a, b, c, and d) which have been tested for validity, reliability, level of difficulty and power difference. The pretest calculation results obtained the average value of the experimental class 40.00 with a standard deviation of 7.17 and the control class 37.10 with a standard deviation of 8.29, based on the normality test Ltabel > Lhitung and the homogeneity test Fcount < Ftable, this shows both classes are normally distributed and homogeneous. Based on the test of the initial ability of tcount < ttable, it states that the two classes are equally capable. Then given a different treatment posttest results obtained the average value of the experimental class obtained 69.71 with standard deviation 6.51 and the control class with an average value of 65.22 with a standard deviation 5.48 from the t test one party obtained tcount > ttable = (2.89 > 1,671) then there is influence a significant Inductive Thinking learning model of student learning outcomes in the material Magnitude and Measurement in class X semester I Medan Parulian 1 High School TP 2019/2020.